Comparison Between IV Lignocaine and IV Labetalol on Hemodynamic Changes during Extubation of Endotracheal Tube - Iqbal, Hira; Askri, Mohsin Riaz; Maqbool, Shumyala; Batool, Abida; Yousafi, Noor Ul Ain (Indus Journal of Bioscience Research, 2025)
Introduction: Laryngoscopy and endotracheal intubation produce pressor and sympathoadrenal reactions. Certain medications, such as Lignocaine and Labetalol, can be given to prevent these haemodynamic alterations before intubation. Objective: The aim of this study was to compare the hemodynamic changes of IV lignocaine and antihypertensive drug during extubation. Materials and Methods: 60 patients of ASA grade I, scheduled for various surgeries under general anesthesia were divided into 2 Groups. Group A was administered I.V plain lignocaine 1.5 mg/kg. Group B was administered IV labetalol 0.5 mg/kg 2 minutes prior to extubation. HR, SBP, DBP was recorded at baseline and 5 min after tracheal extubation. Results: The mean age of patients was 38.07±11.69 years in the Labetalol group and 34.53±6.68 years in the Lignocaine group. Before induction, hemodynamic parameters were comparable. Pre-induction heart rate (HR) was 85.90±9.51 beats/min in the Labetalol group and 87.40±9.12 beats/min in the Lignocaine group. Systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 118.67±11.05 mmHg and 73.87±4.87 mmHg in the Labetalol group, and 122.00±10.30 mmHg and 75.53±4.63 mmHg in the Lignocaine group. Five minutes post-extubation, HR was 90.80±0.99 beats/min in the Labetalol group and 102.50±11.04 beats/min in the Lignocaine group. SBP/DBP were 103.33±7.58 mmHg/71.33±5.76 mmHg in the Labetalol group and 107.67±11.65 mmHg/73.87±5.98 mmHg in the Lignocaine group. These findings align with previous studies, where HR at five minutes post-intubation was significantly lower in the Labetalol group (78.43±6.41 vs. 88.37±6.73 beats/min, p<0.001). Conclusion: Labetalol is a more effective drug in attenuation of hemodynamic response to laryngoscopy and endotracheal intubation in comparison to Lignocaine.